2010
DOI: 10.1097/mcg.0b013e3181b3ab44
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Anticoagulation Therapy With Low Molecular Weight Heparin for Portal Vein Thrombosis in Patients With Liver Cirrhosis

Abstract: LMWH demonstrated safe and effective in the treatment of PVT in patients with liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
149
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(162 citation statements)
references
References 18 publications
6
149
2
1
Order By: Relevance
“…An attractive alternative to oral anticoagulants could be the use of low-molecular-weight heparin (LMWH), the dosing of which is weight based and thus does not necessitate screening. A 50%-80% portal vein recanalization rate was recently reported with the use of LMWH in 38 patients with cirrhosis, with only a few episodes of non-severe variceal bleeding [62,80] . Villa et al [81] performed a randomized controlled trial to evaluate the safety and efficacy of enoxaparin, a LMWH, in preventing PVT in patients with advanced cirrhosis.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…An attractive alternative to oral anticoagulants could be the use of low-molecular-weight heparin (LMWH), the dosing of which is weight based and thus does not necessitate screening. A 50%-80% portal vein recanalization rate was recently reported with the use of LMWH in 38 patients with cirrhosis, with only a few episodes of non-severe variceal bleeding [62,80] . Villa et al [81] performed a randomized controlled trial to evaluate the safety and efficacy of enoxaparin, a LMWH, in preventing PVT in patients with advanced cirrhosis.…”
Section: Treatmentmentioning
confidence: 99%
“…It has also been shown that individuals with PVT at the time of liver transplantation are at higher risk of recurrent PVT after transplantation and of requiring retransplantation [30,70] . The increased mortality and morbidity rates associated with PVT are mostly restricted to the first year after liver transplantation [4,62] and actuarial survival after 1 year is good. Therefore, PVT cannot be considered to be a contraindication to liver transplantation [71] .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were also made in patients not on a waiting list for liver transplantation. Enoxaparin was given at therapeutic doses for 6 months to 28 patients with PVT, after endoscopic variceal eradication [90]. Recanalization was complete, partial and absent in 33.3 %, 50 %, and 16.7 % of patients, respectively.…”
Section: Anticoagulation For the Treatment Of Pvtmentioning
confidence: 99%
“…Yet, at least in the absence of bleeding, there is no data to support withholding anticoagulation from patients with cirrhosis. In general, anticoagulation is safe and well tolerated in cirrhosis [28,29]. Moreover, severity of disease, but not anticoagulation was associated with poor outcome in cirrhosis patients with upper gastrointestinal bleeding [30].…”
Section: Therapeutic Aspects and Recommendations For Cirrhosis Patienmentioning
confidence: 99%